Comparison of on-wafer calibrations for THz InP-based PHEMTs applications*Project supported by the National Natural Science Foundation of China (No. 61275107). (June 2015) - Wang, Zhiming; Huang, Hui; Hu, Zhifu; Zhao, Zhuobin; Wang, Xudong; Luo, Xiaobin; Liu, Jun; Yang, Songyuan; Lü, Xin
Abstract A quantitative comparison of multiline TRL (thru-reflect-line) and LRM (line-reflect-match) on-wafer calibrations for scattering parameters (S-parameters) measurement of InP-based PHEMTs is presented. The comparison is undertaken for the first time and covers a frequency range from 70 kHz to 110 GHz. It is demonstrated that the accuracy of multiline TRL and LRM calibration is in good agreement. Both methods outperform the conventional SOLT calibration in the full frequency band up to 110 GHz. Then the excellent RF performance is obtained by extrapolation on the basis of inflection point, including a maximum current gain cut-off frequency ft of 247 GHz and a maximum oscillation frequency fmax of 392 GHz. The small-signal model based on LRM calibration is established as well. The S-parameters of the model are consistent with the measured from 1 to 110 GHz.